Impact of Green Accounting and Environmental Performance on Financial Performance in the F&B Sector - Anggun Ayu Setyawati; Mahameru Rosy Rochmatullah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the impact of Green Accounting and Environmental Performance on the financial performance of food and beverage manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2022. Grounded in Stakeholder Theory and the Resource-Based View, the research hypothesizes that sustainability initiatives enhance financial outcomes by meeting stakeholder demands and leveraging environmental practices as strategic assets. Using purposive sampling and multiple linear regression, the study finds that Green Accounting positively affects financial performance, reflecting the value of transparency and accountability. However, Environmental Performance, measured through PROPER ratings, shows no significant effect, possibly due to delayed reporting, low public awareness, and limited investor responsiveness to regulatory compliance alone. The study is limited by its narrow industry scope, short observation period, and unexamined external influences such as economic shocks and pandemic-related disruptions. Future research should explore broader sectors, longer timeframes, and additional variables to deepen the understanding of sustainability’s financial implications.